2000
DOI: 10.1046/j.1365-2133.2000.03248.x
|View full text |Cite
|
Sign up to set email alerts
|

The presence of antibodies against virus-like particles of epidermodysplasia verruciformis-associated humanpapillomavirus type 8 in patients with actinic keratoses

Abstract: Epidermodysplasia verruciformis-associated human papillomaviruses (EV-HPVs) are possibly involved in the development of actinic keratoses and may play a part in the pathogenesis of squamous cell carcinoma (SCC) of the skin, as the DNA of these viruses is frequently detected in biopsies of such lesions. Properly designed epidemiological studies, using serological tests to investigate the role of infection with EV-HPVs in cutaneous oncogenesis, are still rare. An IgG-specific enzyme-linked immunosorbent assay us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 21 publications
2
20
0
1
Order By: Relevance
“…A number of different HPV types are found in high percentage of BCC and SCC in immunosuppressed individuals (51). Similarly, a range of HPV types have been isolated from actinic keratoses and SCC from epidermodysplasia verruciformis (EV) patients (52). Furthermore, HPV may likely play a role in these cutaneous carcinomas from immunocompetent non‐EV patients as well (51,53).…”
Section: Discussionmentioning
confidence: 99%
“…A number of different HPV types are found in high percentage of BCC and SCC in immunosuppressed individuals (51). Similarly, a range of HPV types have been isolated from actinic keratoses and SCC from epidermodysplasia verruciformis (EV) patients (52). Furthermore, HPV may likely play a role in these cutaneous carcinomas from immunocompetent non‐EV patients as well (51,53).…”
Section: Discussionmentioning
confidence: 99%
“…There have been few serological investigations into the role of HPV infection in cutaneous SCC. One study found an increased prevalence of antibodies against the EV‐associated HPV 8 in individuals with actinic keratoses [74].…”
Section: Interactions Of P53 With Human Papillomavirusesmentioning
confidence: 99%
“…Infection with human papillomaviruses (HPV) from the beta genus (betaPV) is associated with the development of actinic keratoses and squamous cell carcinoma (SCC) in immune‐competent persons and in organ transplant patients 1–7. The majority of people are infected with multiple betaPV,8 and a substantial proportion of these infections remains detectable over time, indicative of persistent infection 9, 10…”
mentioning
confidence: 99%